Multiphysics‐Enabled Liquid State Thermal Harvesting: Synergistic Effects between Pyroelectricity and Triboelectrification. Issue 10 (8th September 2021) - Chiolerio, Alessandro; Garofalo, Erik; Bevione, Matteo; Cecchini, Luca
Abstract : Energy consumption levels show a never‐ending increase since the industrial era. Toward sustainability objectives, it is of outstanding importance to reduce the amount of wasted energy, that typically comes as waste heat, as a consequence of nonunitary efficiency of any thermodynamic process. Herein, a breakthrough in conversion of low enthalpy heat into electricity is presented, based on a liquid state device that operates through multiphysics effects: thermomagnetic advection, triboelectricity, pyroelectricity, and Ludwig–Sorét effect. A synergistic interaction between ferroelectric surfaces and a complex composition colloidal suspension is evidenced, owing to an enhancement of the generated potential of 365% in comparison with pyroelectric effect and 267% in comparison with triboelectric effect, while the current extracted is 54% higher than the pyroelectric effect only and the power extracted by induction remains substantially unperturbed. The impact of this technology on society is also analyzed, on the basis of a set of practical applications, by means of a computational analysis. Abstract : Mixed composition colloidal suspensions enable a breakthrough in conversion of low enthalpy heat into electricity due to a synergistic combination of pyroelectricity, triboelectricity, density waves, and magnetothermal phenomena.